EVALUASI FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELOLAAN RUSUNAWA (Studi Kasus : Rusunawa Wangurer, Tangkoko dan Unsrat) - Soukotta, Jan; Sompie, Bonny F.; Timboeleng, James A. (Sam Ratulangi University, 2013)
The main problems encountered in the development rusunawa include affordability (ratio of income and expenses), adequacy (quality and density residential) environmental conditions and availability. The research was conducted in rusunawa (Wangurer and Tangkoko) in the municipality of Bitung and rusunawa Unsrat located on the campus UNSRAT Manado.. Secondary data collected through library research and field study. Data processing using analytical hierarchy process (AHP) through expert computer program choice. The results showed that for all three rusunawa, environmental factors (26%) are at the highest value followed occupancy factor (16%), physical utilization factor (14.7%), factor governing body (10.2 %), the economic capacity factor (9.4%), factor the role of local government (8.2%), regulatory factors (8.2%) and social empowerment factor (7.1%). The results per-rusunawa that meets eight factors are rusunawa Tangkoko, followed rusunawa Wangurer and rusunawa Unsrat. In conclusion, environmental factors stated rusunawa third placement on target, flood free, healthy, not adjacent to residential areas, and can be accessed easily with other modes of transportation. Furthermore rusunawa Tangkoko were at the top or the best, because it meets the criteria of the eight factors rusunawa management, followed by rusunawa Wangurer and rental flats Unsrat, not rusunawa. It is recommended that need ongoing socialization of the rules / regulations regarding the management of rusunawa to low income earners (MBR).Keywords: Rusunawa,AHP, MBR